SINGLE NUCLEOTIDE POLYMORPHISMS (CYP11 ALPHA AND CYP17) AND SERUM SEX HORMONE BINDING GLOBULIN LEVELS IN NORMAL AND POLYCYSTIC OVARY SYNDROME - Aziz, Nauman; Doggar, Shamaila; Shoaib, Amer; Aslam, Muhammad Saeed; Altaf, Muhammad Omer (Pakistan Armed Forces Medical Journal, 2021)
Objective: To examine the potential association between CYP11 alpha and CYP17 polymorphism, and serum sex hormone binding globulin (SHBG) levels and their possible contribution to polycystic ovary syndrome.Study Design: Case control study.Place and Duration of Study: University of Health Sciences, Lahore Pakistan, from Jan to Oct 2017.Methodology: A total of 60 cases of polycystic ovary syndrome and 60 controls and single nucleotide polymorphisms were studied for CYP11 alpha (TTTTA)n repeats and CYP17 (-34 T/C) along with sex hormone binding globulin levels and testosterone levels. Data were collected through a specially designed questionnaire. Blood samples were collected followed by serum separation and deoxyribonucleic acid extraction using standard protocols. Serum was used to measure the levels of sex hormone binding globulin and androgens. Extracted deoxyribonucleic acid was screened for the polymorphisms by PCR. SPSS version 20 was used to calculate data statistics.Results: Out of 120 total women, 60 were suffering from polycystic ovary syndrome. Amongst these 60 cases, 43 (71.7%) had changes in menstrual cycle, 36 (60%) with longer than 35 days (p=0.04). Acne (p